The Influence of Audit Fees, The Complexity of The Company's Operations, and Audit Tenure on Audit Report Lag - Mubarok, Fikri; Pahala, Indra; Perdana, Petrolis Nusa (Jurnal Akuntansi, Perpajakan dan Auditing, 2022)
This study aims to analyze the influence of audit fees, the complexity of company’s operations, and audit tenure on audit report lag in consumer non-cyclical sector companies for the period 2018 – 2021. This type of research is quantitative research and the data used is secondary data. The samples used in this study were 33 companies with a total of 132 observational data obtained using a purposive sampling technique. The analytical method used in this study is panel data regression using the E-views 12 application. The results of this study indicate that audit fees and audit tenure have no significant effect on audit report lag, while the complexity of company operations has a significant positive effect on audit report lag.